1999
DOI: 10.1073/pnas.96.17.9944
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric-oxide synthase 2 by aminoguanidine provides neuroprotection of retinal ganglion cells in a rat model of chronic glaucoma

Abstract: Glaucoma is an optic neuropathy with cupping of the optic disk, degeneration of retinal ganglion cells, and characteristic visual field loss. Because elevated intraocular pressure (IOP) is a major risk factor for progression of glaucoma, treatment has been based on lowering IOP. We previously demonstrated inducible nitric-oxide synthase (NOS-2) in the optic nerve heads from human glaucomatous eyes and from rat eyes with chronic, moderately elevated IOP. Using this rat model of unilateral glaucoma, we treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
208
5
7

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(229 citation statements)
references
References 21 publications
9
208
5
7
Order By: Relevance
“…Retinal ganglion cells were identified in rats by retrograde labeling with FluoroGold (Fluorochrome, Inc.) bilaterally injected into the superior collicular brachium (46). FG (5%, 2.4 L/ injection) diluted in saline was microinjected bilaterally into the superior colliculi of anesthetized rats immobilized in a stereotaxic apparatus.…”
Section: Retrograde Labeling Of Retinal Ganglion Cellsmentioning
confidence: 99%
“…Retinal ganglion cells were identified in rats by retrograde labeling with FluoroGold (Fluorochrome, Inc.) bilaterally injected into the superior collicular brachium (46). FG (5%, 2.4 L/ injection) diluted in saline was microinjected bilaterally into the superior colliculi of anesthetized rats immobilized in a stereotaxic apparatus.…”
Section: Retrograde Labeling Of Retinal Ganglion Cellsmentioning
confidence: 99%
“…29, 32, and 33). Recent studies have shown, for example, that treatment with a glutamate antagonist (34) or a nitric oxide synthase inhibitor (35) attenuates RGC death in a rat model of increased IOP. The present finding is potentially of great interest clinically because (i) it shows that neuroprotection can be achieved even when the pressure remains high [indeed, even a pressure reduced to normal is not necessarily safe for patients with glaucoma, in whom the remaining neurons are more vulnerable than normal ones (36)]; and (ii) it is based on a strategy that harnesses and augments the tissue's own defense machinery.…”
Section: Discussionmentioning
confidence: 99%
“…This highly potent secondary oxidant has been implicated in glaucomatous injury (Neufeld et al, 1999).…”
Section: Interplay Of Tnf-α Signaling With Other Cellular Events Assomentioning
confidence: 99%